T. Spawforth, What the Greeks Did For Us. - Roth , Ulrike (Journal of Greek Archaeology, 2024)
Asking after the influence of prior civilisations on modern society is a long-established historical practice, one that regularly spills over into the world of what nowadays may be called popular publication. Open the curtains for What the Greeks Did For Us, Anthony Spawforth’s dazzling tour de force across numerous facets of ancient Greek influence on or, more often, resemblances and receptions in the modern world. Written by one of the great connoisseurs of all things ancient Greek for an ‘informed general readership’ (291), the more than 300 pages go on a treasure hunt after, as the author puts it, ‘the ways in which ancient Greece is present in our culture and society now’ (3, original emphasis).